Optimization of uniaxial tensile stress-strain response of 3D angle interlock woven fabric composite using weft density and draw-in plan variables / Muhammad Nasrun Faris Mohd Zulkifli ... [et al.] - Mohd Zulkifli, Muhammad Nasrun Faris; Yahya, Mohamad Faizul; Zahid, Bilal (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
Currently, 2D woven composites are extensively incorporated into a variety of technical automotive body parts and protective body armor owing to their excellent fabric strength performance. However, there is still a lack of attempts to utilize 3D woven fabrics for the same technical application. Hence, it is vital to examine the fundamental tensile strength of woven fabric composite materials when determining their suitability for end-use applications. This study aimed to investigate the novel effects of two parameters on the uniaxial tensile strength of a high-tenacity polyester three-layer 3D angle interlock (3DAI) woven fabric composite, namely, weave drafting draw-in insertion and weave density. Four different drafting patterns were considered: pointed (DRW 1), broken (DRW 2), broken mirror (DRW 3), and straight (DRW 4), for weft density at 14 and 25 pick.cm-1 . Samples of the 3DAI woven fabric reinforced with epoxy composite at different drafting patterns and weft density combinations were produced and tested. Consequently, the maximum tensile stress and strain were recorded in the woven fabric composite sample with DRW 4 and 25 pick.cm-1 at 113 MPa and 11%, respectively.